Analysis of Electronic Waste Flows and Urban Mining Potential in Surabaya - Rizka Nur Amalia Rachmani; Arseto Yekti Bagastyo (Politeknik Negeri Batam, 2026)
The increase in population, consumption, and technology use has led to a surge in electronic waste, a serious environmental issue. In Indonesia, e-waste management is still primarily handled by the informal sector, with limited regulation and technology, posing risks to the environment and public health. Gunung Anyar District was selected as the study area for this research to analyze household electronic waste flows and the role of the informal sector on urban mining, using Material Flow Analysis (MFA). Potential household e-waste generation was estimated through questionnaires and interviews with 100 households, while additional surveys of the informal sector, TPSSS B3 (Hazardous and Toxic Waste Storage and Management Facility), and waste banks were conducted to trace distribution pathways. Informal sector actors were surveyed using snowball sampling. The potential household e-waste generation in Gunung Anyar is 303.957,35 kg/year. Most e-waste is stored in homes or sold to collectors, with only a small fraction entering waste banks and TPSSS B3. Collectors, both dismantlers and non-dismantlers, act as key nodes in informal urban mining by channeling metal fractions to industries and other collectors, while generating substantial residues that end up at transfer stations and landfills. Although donations and repairs extend product lifespans, a large share of e-waste remains underutilized and environmentally hazardous. These findings highlight the need for stricter regulation and more structured systems to integrate informal actors and reduce environmental and public health impacts.